2006
DOI: 10.1094/phyto-96-0746
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Genetic Exchange by Parasexual Recombination and Genetic Analysis of Pathogenicity and Mating Type of Parasexual Recombinants in Rice Blast Fungus, Magnaporthe oryzae

Abstract: A selectable marker gene conferring resistance to bialaphos (BI) was introduced into rice blast isolate Y90-71BI and another conferring resistance to blasticidin S (BS) into isolate 3514-R-2BS of Magnaporthe oryzae to demonstrate exchange of DNA. Colonies obtained from co-cultures of these two isolates were resistant to both BI and BS and had both resistance genes as shown by Southern blot analysis of their genomic DNA. Conidia from these BI-BS-resistant isolates had only one nucleus per cell after staining wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…We revealed that the segregation of avirulence to virulence (avr/vir) in the progeny derived from crossing Y90-71 and 3514-R-2 on Hattan 3 24 and line K59-1 (unpublished data) was in a 1:1 ratio. The segregation of avr/vir in the parasexual recombinants (BI-BSresistant parasexual recombinants) was consistent with a 1:1 ratio on line K59-1, but not on Hattan 3 15 . We postulated that the segregation of avr/vir of the BI-BS-resistant parasexual recombinants on Hattan 3 was consistent with that of sexual progeny and that the antibiotic-resistance genes and genes for virulence on Hattan 3 might be linked as a result of transformation.…”
Section: Introductionmentioning
confidence: 60%
See 4 more Smart Citations
“…We revealed that the segregation of avirulence to virulence (avr/vir) in the progeny derived from crossing Y90-71 and 3514-R-2 on Hattan 3 24 and line K59-1 (unpublished data) was in a 1:1 ratio. The segregation of avr/vir in the parasexual recombinants (BI-BSresistant parasexual recombinants) was consistent with a 1:1 ratio on line K59-1, but not on Hattan 3 15 . We postulated that the segregation of avr/vir of the BI-BS-resistant parasexual recombinants on Hattan 3 was consistent with that of sexual progeny and that the antibiotic-resistance genes and genes for virulence on Hattan 3 might be linked as a result of transformation.…”
Section: Introductionmentioning
confidence: 60%
“…Mating type was determined by crossing M. oryzae isolates with tester isolates, Y93-164a-1 (MAT1-1, race 132) and Y93-245c-2 (MAT1-2, race 137), as described previously 15 .…”
Section: Mating Type Determinationmentioning
confidence: 99%
See 3 more Smart Citations